1985
DOI: 10.1080/15298668591395210
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Time-Weighted Average as an Index of Exposure and Dose, and of Its Key Elements

Abstract: Time-weighted average (TWA) is widely used in research and practice, in occupational health, as an index of exposure and dose. Its key element, CT, where C is concentration of contaminant and T is duration of contamination, is recognizable as Haber's rule. Neither TWA nor similar measurements have been scientifically validated, and it does not seem appropriately named. In the late 1940s and early 1950s, cautions were expressed about the scientific validity of TWA, but the specific scientific study of it did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…In the absence of knowledge about the dosimetry and mechanism of toxicity of a chemical, timeweighted averaging has also been used as a default approach in estimating safe levels of ambient airborne chemicals (Jarabek, 1995). When the C X t relationship has been examined, however, it has usually been found that C influences toxicity more than t (Atherley, 1985;ten Berge et al, 1986).…”
Section: O 1997 Society Of Toikoksgymentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of knowledge about the dosimetry and mechanism of toxicity of a chemical, timeweighted averaging has also been used as a default approach in estimating safe levels of ambient airborne chemicals (Jarabek, 1995). When the C X t relationship has been examined, however, it has usually been found that C influences toxicity more than t (Atherley, 1985;ten Berge et al, 1986).…”
Section: O 1997 Society Of Toikoksgymentioning
confidence: 99%
“…In the absence of knowledge about the dosimetry and mechanism of toxicity of a chemical, timeweighted averaging has also been used as a default approach in estimating safe levels of ambient airborne chemicals (Jarabek, 1995). When the C X t relationship has been examined, however, it has usually been found that C influences toxicity more than t (Atherley, 1985;ten Berge et al, 1986).The uncertainty associated with risk assessments that are based upon exposure data and rely on Haber's Rule for extrapolation across exposure durations generated the need to examine empirically the relationship between C and t on a relevant functional endpoint. Thus, the major objective of this study was to evaluate whether quantitative exposureeffect modeling could improve the estimation of risk from exposure to a VOC when dosimetric and mechanistic information are lacking.…”
mentioning
confidence: 99%
“…9 Ullvarson & Ovrum (44) Trichl oroethylene 1.3 Fiserova-Berge rova (14) 1. 7 Fis erova-Bergerova (14) 2. 5 Lindqvist (28) 1.…”
Section: Models Of Toxicologic Effectsunclassified
“…Atherley (7) showed that the concept of the timeweighted average (TWA), as a basis for setting limit values, implies that the toxic effects are proportional to CT = k, ie, the product of the exposure concentration (C) and the exposure time (7), where k for a given effect is a constant, this being known as Haber's rule.…”
Section: Models Of Toxicologic Effectsmentioning
confidence: 99%
“…The adjustment of exposure concentration (C) by exposure duration (t) and the calculation of time-weighted averages relies on the assumption, formulated in Haber's Rule (Cx t= k), that the product of exposure concentration and duration produces a constant toxic effect (k). This assumption, however, has a poor scientific basis and limited predictive success (4). As an alternative, Andersen et al (5) advocated adjusting exposure limits over changing exposure durations using physiological pharmacokinetic models and suggested that knowledge about the actions of individual compounds was important in selecting appropriate dosimetry parameters.…”
mentioning
confidence: 99%